Attitudes toward offering genetic counseling for psychiatric conditions among genetics healthcare practitioners in the United Kingdom: A qualitative study. Issue 1 (7th August 2021) - Rowlatt, Amy E.; McAllister, Marion; Cuthbert, Andrew
Abstract: Psychiatric conditions affect a large proportion of the population. High heritability estimates have been reported for commonly diagnosed conditions, suggesting both environmental factors and genetic variation significantly contribute to the chance of psychiatric outcomes. Despite growing interest in the provision and receipt of genetic counseling services for these conditions, such specialized interventions are not routinely available in most healthcare systems, including in the United Kingdom (UK). This study examined the attitudes of fourteen National Health Service employed genetic counselors and clinical geneticists, from seven regional genetic centers, toward offering psychiatric genetic counseling (PGC) in the UK. A qualitative methodology was adopted and individual semi‐structured interviews were conducted either by telephone or face‐to‐face, audio recorded, transcribed in full and analyzed using thematic analysis. Participants' attitudes were organized under three themes: "Demand, " "Readiness to Provide Support, " and "Patient Experience." Participants cited key informational and resource needs which included increased workforce capacity, access to further psychological support for patients and more knowledge about the following: specific genes involved, available genetic testing, recurrence/occurrence risk figures, clinical manifestations, diagnostic criteria, patient concerns associated with the impact of psychiatric conditions and interpersonal skills. While some participants appreciated the value of PGC, some reported apprehension and raised concerns around a lack of available genetic testing, the perceived utility of current management options, and a potential negative psychological impact of PGC. This study identified important barriers to the delivery of PGC in the UK by genetics healthcare practitioners. Our findings highlight the importance of a collaborative, multidisciplinary approach to delivering this intervention and the need for additional training. Further research is required to better understand demand for, nature of, and barriers to provision of PGC in the UK, particularly in terms of genetic counselors' perceptions of their role.